Markers of coagulation and fibrinolysis activation in women with venous thrombolism – phase and extension dependence of the disease process - Stefańczyk, Ludomir; Owczarek, Danuta; Stachowiak, Grzegorz; Grzelak, Piotr (Menopause Review/Przegląd Menopauzalny, 2005)
In 97 women with ultrasonographically diagnosed venous thromboembolism (VTE) some activation markers of coagulation and fibrinolysis systems were under evaluation – then correlation with different VTE stages was estimated. The strongest correlation with the phase and extension of VTE was found in case of D-dimer and PAP, the weakest one in case of F1+2. The above laboratory tests did not allow to differentiate choronic phase of VTE from postthrombothic lesions.